Word Per Minute (WPM) Lampung Script Keyboard - Mardiana; Fahreza Apriyoga Arizal; Meizano Ardhi Muhammad; Martinus; Gita Paramita Djausal (Politeknik Pertanian Negeri Samarinda, 2020)
Users of Font Lampung in previous studies have difficulty in typing because the layout of the Lampung script is complicated to understand. Re-designing the Lampung alphabet keyboard layout allows users to be able to type text in characters more easily. The purpose of this research is to create a Lampung alphabet keyboard layout for more effective typing of the Lampung alphabet. The methods used are UX (User Experience) that are, requirements gathering, alternative design, prototype, evaluation, and result report generation. The layout design is created by eliminating the use of the SHIFT key and regrouping parent letters, the child letters in a more effective composition. The layout design of the Lampung alphabet was printed using the Laser Engraver tool on the keyboard. Through the test, the typing speed increased to 208% of the average value of 62 seconds to 32 seconds. In addition to the results of WPM (Word Per Minute) on keyboard layouts with 8.7 WPM which is faster than previous WPM research but still slower than QWERTY keyboard WPM. Testing of character quality, readability, and difficulty level to know the flaws in the Lampung RaTaYa keyboard layout with good results. This research concludes that the keyboard layout of Lampung RaTaYa is more effective than using the font Lampung script.